INTELLECTUAL CAPITAL, INCOME DIVERSIFICATION AND BANK PERFORMANCE IN INDONESIAS REGIONAL DEVELOPMENT BANKS - Panji Patra Anggaredho; Adler Haymans Manurung; Agung Dharmawan Buchdadi; Muhammad Yusuf (Jurnal Apresiasi Ekonomi, 2024)
Indonesia's economic growth has demonstrated quite impressive achievements in recent years due to the support from the banking sector in stimulating the economy. However, the high performance of the national banking has not been aligned by the Regional Development Banks' (BPD) performances. Thus, this study was conducted to investigate variables that affect BPD performance, such as intellectual capital and income diversification. This study also tested the moderating effect of income diversification between intellectual capital on bank performance. This study used panel data containing financial reports for 23 BPDs in Indonesia. We took annual data from the Financial Services Authority of the Republic of Indonesia with an observation period for the last 16 years (2008-2023). The results of this study show that intellectual capital & income diversification have a positive and significant effect on bank performance. Finally, for testing the moderation effect, this study shows that income diversification provides a moderation effect that can significantly weaken the influence of intellectual capital on bank performance.Keywords: Bank performance, Intellectual capital, Income diversification.